Review of traditional uses, botany, chemistry, pharmacology, pharmacokinetics, and toxicology of Radix Cyathulae - Yongliang Huang; Shanshan Wang; Li Liu; Wei Peng; Jiaolong Wang; Ying Song; Qianghua Yuan; Xing Yuan; Chunjie Wu (BMC, 2019)
Abstract Cyathulae Radix (CR), also known as "Chuanniux" is a well-known traditional Chinese herbal medicine that has been used in China for thousands of years. The present work reviewed advances in traditional uses, origin, chemical constituents, pharmacology, pharmacokinetics, and toxicity studies of CR. This work aims to provide more up-to-date references for modern study and application of this plant. Furthermore, the possible trends and perspectives for future research of this plant are also discussed. In China, the roots of CR have been widely used in clinical practice to treat orthopedic, gynecological, and urologic diseases. Currently, over 59 compounds have been isolated and identified from CR, including alkaloids and flavonoids. The extracts and compounds from CR have many pharmacological activities both in vivo and in vitro. They provide beneficial effects on the hematological system and anti-inflammatory properties. However, few studies have investigated the pharmacokinetics and toxicity of CR. Further studies should be undertaken to investigate the clinical effects, toxic constituents, and pharmacokinetics of CR; perform quality evaluation; and establish quality criteria for processed C. officinalis. Furthermore, studying the changes of raw and processed CR and the variety of this plant between different cultivated areas and cultivars will be interesting.